Gendered resilience pathways – ethnic minorities and climate-smart agriculture in Lao PDR - Farnworth, Cathy Rozel; Douangsavanh, Somphasith; Chanthalath, Ammala; Inphonephong, Souphalack; Sok, Raksa; Kimala, Vidani; Dubois, Mark; Rietveld, Anne (CGIAR GENDER Impact Platform, 2024)
Laos - the Lao People's Democratic Republic (LPDR), established in 1975, is sandwiched between Myanmar, China, Vietnam, Cambodia and Thailand, and is the only landlocked Southeast Asian country. Its landscapes are as diverse as its peoples which include the ethnically dominant Lao Lum and numerous other ethnicities. In 2025, 60% of the population was rural. Irrigated and rainfed rice cultivation is central to the lives of most farmers. People also plant a wide variety of other plants and manage various livestock species, and fish. Traditionally, people have sourced non-timber forest products. Laos is facing a wide number of opportunities and challenges associated with climate variability, changes in hydrology, the Government of Laos’ increasingly diverse privatization strategies, and other factors. Deforestation and monocultural plantations of crops like cassava and sugarcane are increasingly prominent. It is within this socially diverse and ecologically dynamic context that the CGIAR Initiative on Agroecology (AE-I) is implementing an ‘Agroecological Living Landscape’ (ALL) in Laos (AE-I ALL). This is being implemented by the International Water Management Institute (IWMI) with support from WorldFish. It aims to advance progress towards meeting nutritional and economic security through a sustainable and equitable transition towards agroecology. In 2023, the AE-I ALL team decided to deepen its work on understanding and promoting gender equality and social inclusion (GESI). The research package discussed in this report had two elements. The first was to help IWMI to better understand how to develop and implement empowering and socially inclusive agroecological innovations that support the resilience of women and men farmers. Second, the study aimed to field-test a ‘Resilience Pathways Conceptual Framework’ which was developed as part of an evidence synthesis under the CGIAR Initiative on Gender Equality (HER+). This Framework is designed to examine and support ways to work with individual women and men to help strengthen their resilience in the face of climate variability and other challenges, and to move towards improved gender equality and social inclusion. As such the Resilience Pathways Conceptual Framework makes an important contribution to literature: conceptual frameworks focused on establishing individual resilience through a gender lens are very scarce.